Antecedents of maternal pregnancy-related anxiety trajectories: The FinnBrain birth cohort study - Huizink, Anja C. (Wiley, 2025)
Objective: Little is known about the normative courses of pregnancy-related anxiety throughout pregnancy and their antecedents. We examined in a large scale pregnancy cohort which potentially distinct trajectories of pregnancy-related anxiety across pregnancy can be identified, and which factors predict these trajectories.
Methods: A general sample of pregnant women (n = 2928) from the FinnBrain Birth Cohort participated in this study. Several questionnaires were filled in at 14, 24, and 34 weeks of gestation, including the pregnancy-related anxiety questionnaire-revised as main outcome. Latent Growth Mixture Modeling was applied to identify the trajectories of pregnancy-related anxiety across pregnancy, and t-tests and chi-quare tests were conducted to find antecedents of these trajectories.
Results: Two distinct trajectories were identified: (1) a low symptoms group, N = 2594 (88.6%), with lower and slightly increasing levels of pregnancy-related anxiety (2) a moderately-high symptoms group, N = 334 (11.4%) reported higher and slightly decreasing levels of anxiety. Correlates of the moderately-high anxious group included a lower monthly income, drinking alcohol or smoking in early pregnancy, more daily hassles and less joy, more early life adversities, younger age, primiparity, single parenthood, using depression medication, and having higher scores on depression and general anxiety.
Conclusions: Although the majority of pregnant women fall within a low risk trajectory of pregnancy-related anxiety, another group with consistently higher levels of pregnancy anxiety throughout pregnancy may need more clinical attention, as their high pregnancy-related anxiety scores may indicate a risk profile that includes a variety of general and more pregnancy-specific risk factors, which together can negatively affect fetal and infant development and behavior.